Preliminary Study on the Dynamics of Food Delivery Driver - Safira, Fitri (Research Center and Case Clearing House (RC-CCH) - Sekolah Tinggi Manajemen PPM, 2025)
While previous studies have explored the intersection of flexibility and algorithmic control in gig work, there is a notable gap in understanding how drivers strategically manage their idle time, balancing personal autonomy and platform constraints. Additionally, while research has primarily focused on ride-hailing drivers, the experiences of food delivery drivers remain underexplored though it has a unique work environment. This study explores how food delivery drivers in Jakarta manage their daily routines and idle time within the gig economy using a qualitative approach combining non-participatory observations and interviews. The research reveals how drivers navigate idle periods and develop scheduling strategies while working through food delivery apps, shedding light on their time use and work dynamics in this unique context. The findings show that there is a complex interconnection between time, space, and activity, of drivers’ idle time behavior. Furthermore, the research challenges the idea of complete freedom and flexibility in gig work as the scheduling system, designed to reduce idle time, limits drivers’ freedom and flexibility. The result of this study could help platform operators refining their algorithms and support systems to better align driver autonomy with platform objectives, which could improve driver productivity, wellbeing, and satisfaction.